Descartes and the New Horizon of Philosophy - Plečkaitis, Romanas (Problemos, 1998)
Descartes’ Homo cogitans manifested a new understanding of human value. It meant the scientific personality that suggested that science was the highest value, the universal mean of acting and explanation. It was discovered during the time that scientific methods and technology created according to these methods were not the only possible methods which met human requirements and abilities. Science did not recognize, and even suppressed, a large part of human experience, which did not fit into the scientific explanatory framework. Though contemporary Homo cogitans maintains the heritage of Descartes’, who was a critic and doubtful as well, and did not assume the truth so clearly and distinctly, Descartes’ intuition maintained naive and his knowledge seemed to be probabilistic.